2021
DOI: 10.1680/jenge.20.00067
|View full text |Cite
|
Sign up to set email alerts
|

Post Covid-19 water and waste water management to protect public health and geoenvironment

Abstract: The coronavirus disease 2019 pandemic has posed severe threats to humans and the geoenvironment. The findings of severe acute respiratory syndrome coronavirus 2 (Sars-CoV-2) traces in waste water and the practice of disinfecting outdoor spaces in several cities in the world, which can result into the entry of disinfectants and their by-products into storm drainage systems and their subsequent discharge into rivers and coastal waters, raise the issue of environmental, ecological and public health effects. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 88 publications
1
48
0
Order By: Relevance
“…Pathogenic germs such as protozoa and bacteria are also transmitted via the water route and stayed in the gastrointestinal tract of their host (humans and animals) and subsequently released into the environment via feces from where surface and ground waters are polluted ( Paleologos et al, 2020 ). It may also be released into the host's environment through urine and respiratory secretions ( Ghernaout, 2020 ).…”
Section: Viruses Associated With Water Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic germs such as protozoa and bacteria are also transmitted via the water route and stayed in the gastrointestinal tract of their host (humans and animals) and subsequently released into the environment via feces from where surface and ground waters are polluted ( Paleologos et al, 2020 ). It may also be released into the host's environment through urine and respiratory secretions ( Ghernaout, 2020 ).…”
Section: Viruses Associated With Water Pollutionmentioning
confidence: 99%
“…At the moment, the newly discovered strain from the coronavirus family has unquestionably attracted the attention of the world as some studies have reported its detection in wastewater in Netherlands, Australia, USA and Greece ( Paleologos et al, 2020 ; Medema et al, 2020 ; Ahmed et al, 2020 ; Lodder and de Roda Husman, 2020 ). Meanwhile, few reports indicate whether the SARS-CoV-2 can be transmitted via contaminated water ( Adelodun et al, 2020a ; Arslan et al, 2020a ).…”
Section: Viruses Associated With Water Pollutionmentioning
confidence: 99%
“…Untreated wastewater causes major damage to the environment and human health. Therefore, wastewaters should be treated to decrease the spread of diseases and pollution of water resources [21], [22], [23], [24] and [25].…”
Section: Theoretical Explorationmentioning
confidence: 99%
“…The Palestinian healthcare system is currently under pressure and the services provided are to be overwhelmed by It is believed that water and wastewater services in healthcare facilities should be managed differently after the onset of the COVID-19 virus in a developing country with limited technical and financial resources such as Palestine. The novel coronavirus has been detected in the wastewater (Bar Or et al 2020;Farkas et al 2020;Weidhaas et al In review), yet less attention has been paid to the virus migration to water systems (see Bhowmick et al 2020;Paleologos et al 2020). Wastewater epidemiology has been globally used to collect sewage characteristics, monitor infectious disease spread, assess fate and transport of pathogens, control the spread of pandemics (Paleologos et al 2020), determine public health response, and serve as an early warning of outbreaks (Bar Or et al 2020;Bhowmick et al 2020;Weidhaas et al In review).…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus has been detected in the wastewater (Bar Or et al 2020;Farkas et al 2020;Weidhaas et al In review), yet less attention has been paid to the virus migration to water systems (see Bhowmick et al 2020;Paleologos et al 2020). Wastewater epidemiology has been globally used to collect sewage characteristics, monitor infectious disease spread, assess fate and transport of pathogens, control the spread of pandemics (Paleologos et al 2020), determine public health response, and serve as an early warning of outbreaks (Bar Or et al 2020;Bhowmick et al 2020;Weidhaas et al In review). Understanding the characteristics of the novel coronavirus including favored environments and transmission pathways becomes more important to resist its eruption (see Azzi et al 2020;Bhowmick et al 2020;Wang et al 2020;Xiao et al 2020).…”
Section: Introductionmentioning
confidence: 99%